2013
DOI: 10.2174/15733998113099990003
|View full text |Cite
|
Sign up to set email alerts
|

Ayahuasca-Assisted Therapy for Addiction: Results from a Preliminary Observational Study in Canada

Abstract: This form of ayahuasca-assisted therapy appears to be associated with statistically significant improvements in several factors related to problematic substance use among a rural aboriginal population. These findings suggest participants may have experienced positive psychological and behavioral changes in response to this therapeutic approach, and that more rigorous research of ayahuasca-assisted therapy for problematic substance use is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
213
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(238 citation statements)
references
References 50 publications
12
213
0
13
Order By: Relevance
“…Ayahuasca is an Amazonian psychoactive brew made from the Banisteriopsis cappi vine and the Psychotria viridis bush, along with a variety of other Amazonian plants (26), which produces an altered state of consciousness involving perceptual and affective changes (27). Ayahuasca is taken in religious and shamanistic settings, as well as in informal treatment centres (26).…”
Section: Ayahuascamentioning
confidence: 99%
See 1 more Smart Citation
“…Ayahuasca is an Amazonian psychoactive brew made from the Banisteriopsis cappi vine and the Psychotria viridis bush, along with a variety of other Amazonian plants (26), which produces an altered state of consciousness involving perceptual and affective changes (27). Ayahuasca is taken in religious and shamanistic settings, as well as in informal treatment centres (26).…”
Section: Ayahuascamentioning
confidence: 99%
“…One recent observational study found reductions in alcohol, cocaine and tobacco use, and improvements in subjective wellbeing in a sample of 12 people who were treated with ayahuasca for drug problems (27).…”
Section: Ayahuascamentioning
confidence: 99%
“…), suggesting that this approach is not a radical departure from historical practices. That said, rigorously controlled, ethically conducted scientific research into the effects of such drugs on moral learning or other moral outcomes (in concert with appropriate psychosocial and environmental factors) may well be worth pursuing (Tennison, 2012; see also Frecska et al, 2016;Griffiths et al, 2006;Griffiths et al, 2008;Soler et al, 2016;Thomas et al, 2013).…”
Section: Attempted Moral Neuroenhancements Past and Presentmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] We will focus on two classes of psychedelics: classic psychedelics and "entactogens. "…”
Section: Types Of Psychedelic Drugsmentioning
confidence: 99%